Redundancy or progress? A response to Driscoll et al. (2019) - Liliana Katinas; Richard J. Ladle (Journal of Biogeography, 2020)
Driscoll et al. ( Journal of Biogeography , 2019, 46, 2850–2859) provide a critique of ‘Countryside Biogeography’, but also include ‘Conservation Biogeography’ and ‘Agriculture Biogeography’ in their criticisms. Their main thesis is that these new sub‐disciplines offer a ‘conceptual wrapper’ rather than distinctive frameworks and that the consequent redundancy of terms has the potential to sow confusion among biogeographers and slow progress. Here we argue that, far from sowing confusion Conservation Biogeography, for example, has provided important focal points for emerging scientific discourse, promoting new research, spawning undergraduate and graduate courses, and facilitating the formation of new scientific collaborations. The success or failure of a new sub‐discipline depends on its utility. If new framings sow confusion, introduce redundancy and provide no new insights they will not be widely adopted and cited. The development of new sub‐disciplines is a strong indicator of a vibrant, socially relevant and intellectually adventurous research area.